Everything is Noise: Don Delillo’s White Noise and the Affectivity of Media, Religion, and Divination - Chalfant, Eric (Journal of religion, media and digital culture, 2018)
This paper provides a theoretical defense of the concept of noise, borrowed and loosened from the field of information theory, as a heuristic tool for discussing mediation as divination and exploring the intersection of media studies and religious studies. I first provide a theoretical primer for the concept of noise as it is articulated by Claude Shannon and Warren Weaver and developed in media studies by Friedrich Kittler and in religious studies by Mark Taylor. Then, a close reading of Don Delillo’s White Noise draws out the potential of noise to highlight media’s ability to provide spiritual meaning and truth through an affect of divination. Finally, I connect these themes to current conceptions of media’s relationship to truth as well as recent anthropology on religious divination, suggesting the utility of noise to aid in scholarly efforts to materialize both media studies and religious studies as they engage with affect theory.